2005
DOI: 10.1073/pnas.0507777102
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of classical crystal growth theory explain quartz and silicate dissolution behavior

Abstract: The central control of mineral weathering rates on biogeochemical systems has motivated studies of dissolution for more than 50 years. A complete physical picture that explains widely observed variations in dissolution behavior is lacking, and some data show apparent serious inconsistencies that cannot be explained by the largely empirical kinetic ''laws.'' Here, we show that mineral dissolution can, in fact, be understood through the same mechanistic theory of nucleation developed for mineral growth. In princ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
273
1
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(296 citation statements)
references
References 26 publications
20
273
1
2
Order By: Relevance
“…[75] In fact, dry biomass contains about 1.5 wt.% of inorganic salts such as NaCl and the dissolution rate of metal oxides could be dramatically enhanced by cations in solution. [76] Catalytic tests showed that the presence of NaCl had no influence on glucose conversion during the liquid-phase transformation of glucose to HMF on ZSM-5. However, zeolite hydrothermal stability was significantly perturbed by the presence of NaCl, leading to the hydrolytic attack of extra-framework species and/or defects sites.…”
Section: Increasing Support Stability In Hydrothermal Conditionsmentioning
confidence: 96%
“…[75] In fact, dry biomass contains about 1.5 wt.% of inorganic salts such as NaCl and the dissolution rate of metal oxides could be dramatically enhanced by cations in solution. [76] Catalytic tests showed that the presence of NaCl had no influence on glucose conversion during the liquid-phase transformation of glucose to HMF on ZSM-5. However, zeolite hydrothermal stability was significantly perturbed by the presence of NaCl, leading to the hydrolytic attack of extra-framework species and/or defects sites.…”
Section: Increasing Support Stability In Hydrothermal Conditionsmentioning
confidence: 96%
“…The kinetics of new kink formation (surface nucleation) was hypothesized to depend on the frequency of water exchange between a building unit and a bulk fluid (Kowacz and Putnis, 2008). It has been shown that changing the properties of the aqueous solvation environment by organic additives as well as simple inorganic salts can result in modification of the reaction rates as well as modes of crystal dissolution and growth, surface features, bulk crystal morphology and impurity incorporation even if the thermodynamic driving force is kept constant (De Yoreo and Dove, 2004;Dove et al, 2005;Piana et al, 2006Piana et al, , 2007Kowacz et al, 2007). The influence of the ionic strength on precipitation kinetics was found to be in agreement with the Bronsted-Bjerrum theory that relates reaction rates with polar properties of the solvent (salt medium effect) and the consequential hydration of ions (Zuddas and Mucci, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Systematic investigations of solution composition effects are rare. Attempts to derive empirical or theoretical linkages between multiple regions of solution saturation state are rare (Nagy and Lasaga 1992;Dove et al 2005). No theory has yet been formulated to apply to all minerals in all solutions.…”
Section: Scientific Challengesmentioning
confidence: 99%